FAKTOR-FAKTOR YANG MEMENGARUHI CAPAIAN LITERASI MATEMATIKA SISWA INDONESIA DALAM PISA 2012 - Rogers Pakpahan (Jurnal Pendidikan dan Kebudayaan, 2016)
In order to obtain information on the quality of education and the system education that are underway in various countries, it is conducted international studies called Programme for International Student Assessment (PISA). This study aims to determine the factors that affect student background of literacy mathematics achievement by PISA 2012. The study population was 15 years old Indonesian student. Samples were 5622 students of 15 year old students spread across 31 provinces. The sampling and data collection is determined by PISA in 2012 with a random sampling conducted by multilevel, clustering, and stratified. PISA data collection instruments consist of test capabilities (learning achievement) and questionnaires. The results showed that the factors that affect literacy mathematics achievement of PISA 2012 are the background from internal factors such as the personal character (discipline) of the student and external factors such as the condition of the family, ownerships of the means of learning, and social and cultural conditions at home. The study concluded that character, socio-economic and cultural conditions, computer ownership, and text book are the main factors that affect Indonesian studentsâ€™ mathematics literacy achievement of PISA 2012.Â ABSTRAKKajian ini bertujuan untuk mengetahui faktor-faktor latar belakang yang memengaruhi capaian literasi Matematika siswa Indonesia yang menjadi peserta studi PISA 2012. Populasi penelitian adalah siswa Indonesia yang berusia 15 tahun. Sampel penelitian yakni siswa berusia 15 tahun sebanyak 5.622 orang yang tersebar di 31 provinsi. Penentuan sampel dan pengambilan data ditentukan oleh PISA tahun 2012, dengan teknik random sampling yang dilakukan dengan cara multilevel, clustering, dan stratified. Hasil penelitian menunjukkan bahwa faktor-faktor yang memengaruhi prestasi siswa Indonesia pada studi PISA 2012 yaitu latar belakang peserta dari faktor internal yaitu jati diri siswa dan faktor eksternal yaitu kondisi keluarga, kepemilikan sarana belajar, dan kondisi sosial budaya di rumah. Penelitian menyimpulkan bahwa jati diri, kondisi sosial ekonomi dan budaya, kepemilikan komputer, dan buku-buku merupakan faktor utama yang memengaruhi capaian literasi matematika siswa Indonesia peserta PISA 2012.